(untitled) (Global Conference on Medical and Health Sciences, 2026)
The integration of artificial intelligence (AI) into neurosurgical practice has significantly improved diagnostic precision, surgical planning, and outcome prediction. However, the “black-box” nature of many advanced machine learning models has limited their clinical adoption due to a lack of transparency and interpretability. In high-risk domains such as neurosurgery, where decisions directly impact patient survival and neurological function, the need for explainable and trustworthy AI systems is critical.